Echocardiographic evaluation of heart valve prosthetic dysfunction - Yuriy Ivaniv (Heart Vessels and Transplantation, 2018)
Patients with replaced heart valve submitted to echocardiographic examination may have symptoms related either to valvular malfunction or ventricular dysfunction from different causes. Clinical examination is not reliable in a prosthetic valve evaluation and the main information regarding its function could be obtained using different cardiac ultrasound modalities. This review provides a description of echocardiographic and Doppler techniques useful in evaluation of prosthetic heart valves. For the interpretation of echocardiography there is a need in special knowledge of prosthesis types and possible reasons of prosthetic function deterioration. Echocardiography allows to reveal valve thrombosis, pannus formation, vegetation and such complications of infective endocarditis as valve ring abscess or dehiscence. Transthoracic echocardiography requires different section plane angles and unconventional views. Transesophageal echocardiography is more often used than in native valve examination due to better visualization of prosthetic valve structure and function. Three-dimensional echocardiography could provide more detailed visual information especially in the assessment of paravalvular regurgitation or valve obstruction.